2014
DOI: 10.1002/2014jd021557
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of sublimation in the dry snow zone of the Greenland ice sheet in a warming world

Abstract: Meteorological and glaciological data obtained over an intensive 2 year measurement period (2000)(2001)(2002) are used to run a physically based climatic mass balance model to characterize a seasonal variability in mass and energy exchanges at Summit, Greenland. The model resolves the full surface energy balance and the subsurface temperature profile by inclusion of energy release from penetrating shortwave radiation. A Monte Carlo approach using 1000 different parameter combinations is adopted to assess model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 111 publications
(153 reference statements)
5
45
1
Order By: Relevance
“…Averaged gradients between the surface and the lower measurement height during the IOP were 1.6 s −1 , 0.3 • C m −1 , and −0.15 hPa m −1 , respectively. The value for vapor pressure is very close to that obtained at Summit during 2000-2002 as reported by Cullen et al (2014). However, averaged gradients between the lower and upper measurement heights were nearly 0, except for the case of wind speed, for which it was 0.2 s −1 .…”
Section: Uncertainties Caused By the Latent Heat Flux Calculation Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Averaged gradients between the surface and the lower measurement height during the IOP were 1.6 s −1 , 0.3 • C m −1 , and −0.15 hPa m −1 , respectively. The value for vapor pressure is very close to that obtained at Summit during 2000-2002 as reported by Cullen et al (2014). However, averaged gradients between the lower and upper measurement heights were nearly 0, except for the case of wind speed, for which it was 0.2 s −1 .…”
Section: Uncertainties Caused By the Latent Heat Flux Calculation Methodssupporting
confidence: 87%
“…Comparison between OBS_2LM and OBS_1LM shows that the former obviously tends to be higher than the latter, and sometimes the signs of the fluxes are different. According to previous studies Cullen et al, 2014), the sign and magnitude of the latent heat fluxes from the 1LM and 2LM methods agree reasonably at low elevations on the GrIS, whereas they often differ from each other at the higher elevations. Measurements conducted previously in the northwest GrIS (the Humboldt and GITS sites) showed that the net annual sublimation from the 1LM and 2LM methods did not agree sufficiently at both sites ).…”
Section: Uncertainties Caused By the Latent Heat Flux Calculation Methodssupporting
confidence: 55%
“…The model structure used in this study is explained in detail by Mölg et al (2012) with the latest model version (2.4) used by Mölg (2015). The model calculates the surface and near-subsurface mass and energy fluxes and has been successfully applied to address various questions in a range of climatic conditions (Collier et al, 2013;Conway and Cullen, 2015;Cullen et al, 2007Cullen et al, , 2014Gurgiser et al, 2013a, b;MacDonell et al, 2013;Mölg et al, 2014;Nicholson et al, 2013). The model computes the mass balance as the sum of solid precipitation, surface deposition, internal accumulation (refreezing of liquid water in snow), change in englacial liquid water storage, subsurface and surface melt, and sublimation.…”
Section: Mass and Energy Balance Modellingmentioning
confidence: 99%
“…The model of this linkage is described in detail in Mölg et al . [, 2012] and has been applied to various questions and climatic environments around the world [e.g., Conway and Cullen , ; Gurgiser et al ., ; MacDonell et al ., ; Nicholson et al ., ; Cullen et al ., ; Mölg et al ., ]. Therefore, only a brief model description is given here.…”
Section: Methods Model and In Situ Measurementsmentioning
confidence: 99%